Responses to small town change : a case study of Pātea : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Geography, College of Humanities and Social Sciences, Massey University, Te Kunenga Ki Pūrehuroa, Palmerston North, New Zealand - Lilly, Ben Ashley (Massey University, 2024)
This thesis works to understand responses to small town change and discuss these in the context of existing geographic literature. It approaches the New Zealand small town of Pātea and explores a variety of identities and perspectives from those who live there. During this research, I carried out a media analysis and semi-structured interviews with Pātea community leaders. Using this context of Pātea, I discussed existing small-town literature, as the case study provided insights into strengths and limitations therein. This thesis found that discourse around Pātea tends to focus on the economic environment, whereas the people of Pātea continue to define their town in broader terms, and towards more cultural and community-focussed ideals. Many view Pātea in relation to the closing of the freezing works in 1982, and subsequent decline in employment and local business – but such perspectives often impose deterministic views on growth and development on the town, ignoring the realities of pride and place attachment which thrive – including with the ongoing influence of Pātea Māori Club and their song Poi E. It was also found the town has a powerful sense of empowerment and activism, which will define future opportunities such as for offshore windfarming. Through these findings, it is proposed that the academic term ‘left behind’ might be replaced with ‘left out’, to encompass landscapes beyond models of linear economic progression. I also suggest the future of Pātea is optimistic, and that there are opportunities for Pātea to demonstrate ‘more-than-capitalist’ economies for the rest of New Zealand to see – but that researchers and media commentators have a responsibility to represent Pātea in more than just economic terms.
Keywords: 440610 Social geography